PENGARUH MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR SISWA KELAS V PADA PEMBELAJARAN TEMATIK SEKOLAH DASAR - Simarmata, Ester Julinda; Siburian, Adi Susanto; Ambarwati, Nova Florentina; Lumbanraja, Bogor; Sari, Heka Maya; Tanjung, Darinda Sofia (Universitas Negeri Medan, 2024)
This research aims to determine the influence of the Team Assisted Individualization (TAI) Cooperative Learning Model on Student Learning Outcomes in Theme 8 Our Friend's Environment Class V of State Elementary School 155701 Pahieme 2 Learning Year 2023/2024. The research method used is an experimental method with a quantitative research type. The total research sample was 30 students based on purposive sampling technique. To determine students' initial abilities, the research conducted a Pre Test with an average score of 52.63 which was in the poor category. The results of the Post Test have improved from the Pre Test results given previously with the students' average score reaching 75.53 in the good category. It can be said that the level of success in student learning outcomes has increased as evidenced by the results of the correlation coefficient test calculation, which obtained r_count ≥ r_tabel with results of 0.766 ≥ 0.361. Next, hypothesis testing is comparing the t_count≥ t_table values. The obtained value of t_count = 6.311 while t_table = 1.697. Because t_count ≤ t_table (6.311 ≥ 1.697) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Team Assisted Individualization type cooperative learning model on student learning outcomes.